Internal Migration, Urbanization and Poverty in Asia: Dynamics and Interrelationships - Jayanthakumaran, Kankesu; Verma, Reetu; Wan, Guanghua; Wilson, Edgar (Springer Nature, 2019)
Development Economics;Economic Policy;Asian Economics;Economics;Economy-wide Country Studies;Internal migration, urbanization and poverty in Asia;Poverty as an urban issue;Poverty measures in Asia;Rural-urban migration in Asia;Internal migration and employment in Asia;Urban economic growth;Income polarization in Asia;Open access;Development economics & emerging economies;Political economy